PERTUMBUHAN DAN KELANGSUNGAN HIDUP IKAN PATIN (Pangasius SP.) DI SISTEM RESIRKULASI DENGAN PADAT TEBAR BERBEDA - Annisa Septimesy; Dade Jubaedah; Ade Dwi Sasanti (Jurnal Akuakultur Rawa Indonesia, 2016)
ABSTRACT The purpose of this study was to observe the effect of stocking density on the growth and survival of catfish (Pangasius sp.) 3 ± 0,5 cm in a recirculation system with water flow of 0.1 L.sec-. This study was conducted in May - June 2016 in the Basic Laboratory of Fisheries, University of Sriwijaya. The research method used a completely randomized design with three treatments and three replications. The treatment were stocking density of fish 20 ind.L-1 (P1),30 ind.L-1 (P2),and 40 ind.L-1 (P3). Parameters observed were fish growth, survival rate and water quality. The results showed that the different stocking density on a recirculation system with water flow 0.1 L.sec-1 did not significantly different to the survival rate. In this research P1 treatment with stocking density 20 fish.L-1was the best treatment, with absolute weight growth 1.03 ± 0.43 g, absolute length growth 1.86 ± 0.50 cm, and survival rate 73.34 ± 4.30 %. Keywords : Stocking density, Recirculation system, Pangasius sp.